STEM Learning for Science Education Program: Reference to Indonesia - Riandi; Oktian Fajar Nugroho; Anna Permanasari; Harry Firman (Universitas Kanjuruhan Malang, 2021)
STEM education has now become a concern for researcher of education to be considered as a highly demanding learning. In Southeast Asia, Indonesia is one of the largest countries that has a lot of human resources that need to be improved in skills and abilities. This study aims to examine whether the urgency of STEM learning in Indonesia by looking at 21st century skills, this study uses content analysis methods, including examining the best implementation of STEM education aimed at teachers by investigating technical design skills training for teachers and students and also reviewed the literature from previous research from 1990 to 2016 which focused on developing STEM learning education throughout the world. In this study it was found that STEM education showed very significant developments throughout the world and had a major impact in efforts to improve students' understanding of concepts, literacy and creativity. From various research sources have provided evidence that implementation in implementing STEM Education to teachers. STEM is an application of daily life that is close and increases students' awareness of the environment.